Modified Atmosphere Packaging on Physico-Chemical Characteristics of Star Apple (Chrysophyllum cainito) Fruit during Post-harvest Storage - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2020)
Star apple (Chrysophyllum cainito) is popularly cultivated in Mekong region. Its pulp has strong sweet taste with antioxidant constituents contributing to various phytochemical and functional advantages. However this fruit has a short shelf life due to its perishable nature. It’s necessary to have appropriate way to extend its commercial distribution. Modified atmosphere packaging can be considered as a proper alternative to store this perishable fruit. Purpose of this research focused on the application of modified atmosphere packaging (MAP) to prolong shelf-life of star apple fruit. Weight loss (%), firmness (N), total soluble solid (oBrix), and vitamin C (mg/100g) were the main variables applied to observe this valuable fruit during 21 days of storage. Under MAP (30% CO2, 15% O2, 55% N2), star apple fruit could be extended to 18 days regarding to the weight loss, firmness, total soluble solid, and vitamin C values. Our finding contributed a basic foundation for more further studies on other tropical fruits and vegetables. Keywords: Chrysophyllum cainito, Modified atmosphere packaging, Weight loss, Firmness, Soluble solid, Vitamin C.